Interaction of Bovine Peripheral Blood Polymorphonuclear Cells and Leptospira Species; Innate Responses in the Natural Bovine Reservoir Host - Wilson-Welder, Jennifer H.; Frank, Ami T.; Hornsby, Richard L.; Olsen, Steven C.; Alt, David P. (Frontiers in Microbiology, 2016)
Cattle are the reservoir hosts of Leptospira borgpetersenii serovar Hardjo, and can also be reservoir hosts of other Leptospira species such as L. kirschneri, and L. interrogans. As a reservoir host, cattle shed Leptospira, infecting other animals, including humans. Previous studies with human and murine neutrophils have shown activation of neutrophil extracellular trap or NET formation, and upregulation of inflammatory mediators by neutrophils in the presence of Leptospira. Humans, companion animals and most widely studied models of Leptospirosis are of acute infection, hallmarked by systemic inflammatory response, neutrophilia and septicemia. In contrast, cattle exhibit chronic infection with few outward clinical signs aside from reproductive failure. Taking into consideration that there is host species variation in innate immunity, especially in pathogen recognition and response, the interaction of bovine peripheral blood polymorphonuclear cells (PMNs) and several Leptospira strains was evaluated. Studies including bovine-adapted strains, human pathogen strains, a saprophyte and inactivated organisms. Incubation of PMNs with Leptospira did induce slight activation of neutrophil NETs, greater than unstimulated cells but less than the quantity from E. coli P4 stimulated PMNs. Very low but significant from non-stimulated, levels of reactive oxygen peroxides were produced in the presence of all Leptospira strains and E. coli P4. Similarly, significant levels of reactive nitrogen intermediaries (NO2) was produced from PMNs when incubated with the Leptospira strains and greater quantities in the presence of E. coli P4. PMNs incubated with Leptospira induced RNA transcripts of IL-1β, MIP-1α, and TNF-α, with greater amounts induced by live organisms when compared to heat-inactivated leptospires. Transcript for inflammatory cytokine IL-8 was also induced, at similar levels regardless of Leptospira strain or viability. However, incubation of Leptospira strains with bovine PMNs did not affect Leptospira viability as measured by limiting dilution culture. This is in contrast to previously reported results of innate inflammatory activation by Leptospira in human and other animal models, or the activation and interaction of bovine PMNs with Escherichia coli and other bacterial pathogens. While it could be hypothesized that variations in innate receptor recognition, specifically variance in toll-like receptor 2, could underlie the observed reduction of activation in bovine